Особливості замісної терапії вродженої дисфукції кори надниркових залоз у дітей - Зелінська, Н. Б.; Погадаєва, Н. Л.; Глоба, Є. В.; Шевченко, І. Ю. (Clinical Endocrinology and Endocrine Surgery, 2014)
The article presents literature and own data on inadequate treatment of children with congenital adrenal hyperplasia (CAH). The necessity to identify hidden mineralocorticoid deficiency for stable compensation in hormonal parameters without an overdose of glucocorticoids , as well as testicular ultrasound of all boys with CAH for early detection of tumors of testicular tissue was proved. early Closure of the growth zones in chronic disease decompensation was confirmed.